Draft Annual Plans 1993-94, 1994-95 and 1995-96 Government of Punjab - Planning Commission (Planning Commission, 1993)
Total Plan outlay for three years 1993- 96 is proposed at Rs. 5000 crore. the year wise outlay for 1993-94, 1994-95 and 1995-96 is Rs. 1500.00 crore, Rs. 1677.15 crore and Rs. 1822.85 crore respectively. Major thrust area is power sector which covers 43% of the total outlay of Rs. 5000 crore. Ranjit Sagar Project (600 MW, Punjab's share 452MW), Shahpur Kandi Project (168MW) and GNDTP-III(210MW) are proposed to be completed by 1996-97.
Government of Punjab, Department of Planning